Classification of patients with cold sensation by a review of systems database: A single-centre observational study. (August 2019) - Yoshino, Tetsuhiro; Katayama, Kotoe; Yamaguchi, Rui; Imoto, Seiya; Miyano, Satoru; Mima, Hideki; Watanabe, Kenji
Highlights: Appropriate herbal formula is determined on the basis of the patient's traditional medicine pattern (TM1). Importance of accompanying symptoms in diagnosing a traditional medicine pattern(TM1) has not been well demonstrated. Evaluation of the patients' subjective symptoms recorded on e-questionnaire. Patients with a qi stagnation pattern had higher rates of depression and insomnia. Patients with a blood stasis pattern, had higher rates of acne, body stiffness, and menstrual abnormality. Abstract: Objectives: In Kampo medicine, a traditional medicine pattern (TM1) refers to the complete clinical presentation of the patient at a given moment in time. Candidate herbal formulas are chosen for a chief complaint, and an appropriate formula is determined on the basis of the pattern (TM1) diagnosis. In this study, we demonstrated the importance of accompanying symptoms in diagnosing traditional medicine patterns (TM1) . Design: Single centre observational study. Setting: We analysed data from 524 new patients with a hypersensitivity to cold sensation as their primary diagnosis (mean age 51.6 ± 17.8 years; female ratio 82.1%) who visited the Keio University Hospital Kampo Clinic between 2008 and 2013. Main outcome measures: Accompanying symptoms were recorded on the browser-based e-questionnaire system, which contained 128 items. The Japan Society for Oriental Medicine's board certified Kampo specialists diagnosed the traditional medicine patterns (TM1) . Results: When participants were classified according to the origin of their cold sensation, there were no differences in their traditional medicine patterns. In contrast, when patients were classified based on the number of accompanying symptoms, a significant difference in the patterns was identified. An increasing number of accompanying symptoms was associated with more frequent qi stagnation and blood stasis pattern (TM1) . Patients with a qi stagnation pattern had higher rates of depression and insomnia. In contrast, patients with a blood stasis pattern (TM1), had higher rates of acne, body stiffness, and menstrual abnormality. Conclusions: Qi stagnation and blood stasis patterns (TM1) are related to a number of different accompanying symptoms in the patients with hypersensitivity to cold sensation.